Metacognition vulnerabilities in time of crisis: Who to protect from suicidal risk?. Issue 12 (11th November 2022) - Martin, Sylvia; Oltra, Anna; del Monte, Jonathan
Abstract: Introduction: During stressful events, we are all trying to cope. We may not be equal depending on our emotional, psychological, and mental states. During the COVID‐19 pandemic, we could try to avoid negative information processing and anxiogenics content to prevent unhealthy thinking processes. One of the processes we can observe regarding our way of thinking and its impact on our psychological well‐being is Metacognition. Methods: We recruited 104 outpatients in 2018. In 2020, during the pandemic, we recruited 216 outpatients and 176 healthy controls. We assessed their level of metacognition with the MCQ30 scale together with Suicidal risk and Hopelessness. Results: All three groups showed significant differences, with the nonclinical sample having higher scores in MCQ30. Regression revealed the different profiles where Hopelessness was the only predictor for the clinical sample, whereas metacognition was an adjunctive predictor of suicidal risk for the nonclinical sample. Conclusion: Our results showed that the COVID‐19 crisis influenced metacognitive levels for the nonclinical sample but not for the clinical population. Moreover, Hopelessness predicted suicide risk for both populations, but Metacognition was also a predictive factor for the nonclinical sample. We conclude with the possible impact of preventive measures based on Metacognitive work that can be created out of these results. Abstract :